Leptomeningeal myelomatosis with hypertrophy of the cauda equina nerve roots: A case report. Issue 6 (9th August 2020) - Sugimoto, Takamichi; Takasuka, Hiroki; Ishikawa, Ruoyi; Tazuma, Taku; Hayashi, Masahiro; Mine, Naoko; Naito, Hiroyuki; Nomura, Eiichi; Shiote, Yasuhiro; Yamawaki, Takemori
Abstract: Patients with multiple myeloma often have neurologic complications, but infiltration of the leptomeninges is rare. We present a case of difficulty walking with multiple myeloma and leptomeningeal myelomatosis, which was characterized by cauda equina hypertrophy. Sciatica and positive straight leg raising test were accompanied with hypertrophy. This highlights the importance of consideration for MRI imaging to detect cauda equina lesion in patients of difficulty walking with multiple myeloma.